2017
DOI: 10.1038/s41598-017-02042-2
|View full text |Cite
|
Sign up to set email alerts
|

Production of three phenylethanoids, tyrosol, hydroxytyrosol, and salidroside, using plant genes expressing in Escherichia coli

Abstract: Polyphenols, which include phenolic acids, flavonoids, stilbenes, and phenylethanoids, are generally known as useful antioxidants. Tyrosol, hydroxytyrosol, and salidroside are typical phenylethanoids. Phenylethanoids are found in plants such as olive, green tea, and Rhodiola and have various biological activities, including the prevention of cardiovascular diseases, cancer, and brain damage. We used Escherichia coli to synthesize three phenylethanoids, tyrosol, hydroxytyrosol, and salidroside. To synthesize ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
82
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(84 citation statements)
references
References 39 publications
1
82
1
Order By: Relevance
“…The resulting strain did not synthesize detectable levels of avn F, but anthranilate and caffeic acid were found in the culture filtrate. A similar phenomenon was previously observed for the synthesis of hydroxysalidroside, in which the introduction of one additional gene in the stepwise synthesis interfered with the whole reaction, resulting in no product formation [35]. Another possible explanation is that HCBT used caffeic acid less effectively than p -coumaric acid (Table 3), while the attachment of CoA into either p -coumaric acid or caffeic by 4CL was similar [36].…”
Section: Resultssupporting
confidence: 67%
“…The resulting strain did not synthesize detectable levels of avn F, but anthranilate and caffeic acid were found in the culture filtrate. A similar phenomenon was previously observed for the synthesis of hydroxysalidroside, in which the introduction of one additional gene in the stepwise synthesis interfered with the whole reaction, resulting in no product formation [35]. Another possible explanation is that HCBT used caffeic acid less effectively than p -coumaric acid (Table 3), while the attachment of CoA into either p -coumaric acid or caffeic by 4CL was similar [36].…”
Section: Resultssupporting
confidence: 67%
“…With the glycosyltransferase OsUGT13 from rice we here identified an alternative UGT, which was more suitable for glycosylation of tyrosol both in S. cerevisiae and C. glutamicum. Recently, and after we had finished our screening of UGTs, another salidroside pathway was reconstituted in E. coli, using a combination of various plant genes (Chung et al, 2017). In this study, UGT85A1 from Arabidopsis (Arabidopsis thaliana), which showed essentially full conversion of tyrosol to salidroside, allowed for product titers of up to 0.97 mM (290 mg L 21 ) after 48 h of cultivation.…”
Section: Discussionmentioning
confidence: 95%
“…In another study, Aro8 and Aro10 from S. cerevisiae were overexpressed in E. coli and pheA and feaB were deleted, resulting in the synthesis of 4.15 mM tyrosol upon supplying 10 mM tyrosine [43]. By introducing the bifunctional gene AAS into E. coli and engineering the E. coli tyrosine biosynthesis pathway to increase intracellular tyrosine concentration by deleting tyrR and pheA, 3.77 mM tyrosol was synthesized [44]. When more genes (tyrA, ppsA, tktA, aroD, and aroB) of the shikimate pathway of E. coli (Fig.…”
Section: Phenylethanoid Synthesis In Microorganismsmentioning
confidence: 99%
“…The UGTs found so far attach glucose to both the phenolic hydroxyl group and alcoholic hydroxyl group. Chung et al [44] screened Arabidopsis thaliana UGTs to synthesize salidroside from tyrosol and found that AtUGT73C5, AtUGT73C6, and AtUGT85A1 specifically synthesized salidroside, and that AtUGT84A1 showed the highest production of salidroside. AtUGT84A1 also converted hydroxytyrosol into salidroside [49].…”
Section: Phenylethanoid Synthesis In Microorganismsmentioning
confidence: 99%
See 1 more Smart Citation